Renewable Resources and Biorefineries - Jacob-Lopes, Eduardo; Queiroz Zepka, Leila (IntechOpen, 2019)
Renewable Resources and Biorefineries presents an authoritative and comprehensive overview of biobased technologies for the production of fuels, food/feed, and materials. This book provides an insight into future developments in each field and an extensive bibliography. It will be an essential resource for researchers and academic and industry professionals in the renewable resources field.